Durable disease control and refractory bullous pemphigoid after immune checkpoint inhibitor discontinuation in metastatic renal cell carcinoma: A case report - Mari, Roxane; Guerin, Mathilde; Vicier, Cécile; Walz, Jochen; Bonnet, Nathalie; Pignot, Géraldine; Gravis, Gwenaelle (Frontiers in Immunology, 2022)
Abstract Background: Immune checkpoint inhibitors deeply modified metastatic renal cell carcinoma’s management, and confront us to adverse events that we were not used to with conventional anti-cancer therapies. We report the case of a patient who received nivolumab as second-line treatment of a metastatic clear cell renal cell carcinoma and who developed bullous pemphigoid four years after nivolumab introduction, with persistent exacerbations even after its discontinuation. Case presentation: A 66-year-old man was diagnosed with lung metastasis eight years after radical nephrectomy for a clear cell renal cell carcinoma. He firstly received an anti-angiogenic agent combination, and then received anti-programmed death 1 (PD1) nivolumab as second-line treatment. Nivolumab led to prolonged disease control, but after four years of exposure the patient developed skin lesions consistent with bullous pemphigoid. After seven years of nivolumab administration and perfect disease stability, nivolumab was discontinued and surveillance was proposed. Despite nivolumab discontinuation, the patient continued to develop bullous pemphigoid exacerbations. Metastatic renal cell carcinoma was still perfectly stable more than two years after immune checkpoint discontinuation with no further anti-cancer therapy. Discussion: We report the case of a refractory bullous pemphigoid which occurred four years after nivolumab introduction and lasted despite nivolumab discontinuation, in a patient whose metastatic renal cell carcinoma is still controlled after more than two years without any anticancer treatment. This highlights the potential association between immune-related adverse events and response to immune checkpoint inhibitors, and underlines the occurrence of late-onset and long-lasting immune-related adverse events even after discontinuation of treatment, which must encourage us to remain vigilant in the long term.